MODEL PENGUKURAN KEPUASAN PELANGGAN PERUMAHAN TIPE 70-350 M2 DI TIGA PERUMAHAN DI SURABAYA DAN SIDOARJO - Hartanto, Andreas (JURNAL DIMENSI UTAMA TEKNIK SIPIL, 2015)
ABSTRACT: Property plays important role in economy business activities. In 2013 property grows by 800,000 units per year, while the supply capacity is only 300,000 units per year. This fact makes the property growth become more interesting. This growth is supported by the middle class growth that reaches 100 million people in 2013 and is estimated to be 141 million people in 2020. Previous research is done on one residential area. This research aims to develop a residential satisfaction measurement model of middle class residential customers in Surabaya-Sidoarjo. This study is different from the previous one in that this research conducts survey on 3 residential complexes and utilizes more comprehensive model. 226 respondents from 3 residential areas in Surabaya-Sidoarjo were collected. The implication of this study is to give the information about the variables that are significant, the level of satisfaction of the consumers on those variables, and improvement priority for developers.The measurement model consists of 8 service quality variables and 9 product quality variables. Our finding shows that assurance and responsiveness are the most important variables in service quality. In product quality dimension, conformance and reliability are the most important variables. In addition, all developers need to improve empathy as the top priority of service quality, while features, serviceability and conformance are the top priority for improvement in terms of product quality.